Efficacy of rhythmical massage in comparison to heart rate variability biofeedback in patients with dysmenorrhea—A randomized, controlled trial. (February 2019) - Vagedes, Jan; Fazeli, Aurelia; Boening, Anna; Helmert, Eduard; Berger, Bettina; Martin, David
Highlights: As widely reported, many women experience menstrual pain. What complementary efforts might aid in reduction of pain in women with dysmenorrhea? Rhythmical massage and HRV biofeedback are used for pain reduction. Evidence is mainly anecdotal regarding efficacy in women with dysmenorrhea. This study gives preliminary evidence that rhythmical massage might improve pain intensity after 12 weeks compared to usual care. Abstract: Background: 20–90% of all women suffer from dysmenorrhea. Standard therapy of primary dysmenorrhea (PD) are NSAIDs and oral contraceptives, effective but not without possible side effects. Objective: To examine the efficacy of rhythmical massage (Anthroposophic Medicine) and heart rate variability biofeedback compared to usual care (control group) on pain intensity in women with primary dysmenorrhea. Methods: This was a three-arm randomized controlled study. Both interventions (rhythmical massage once a week or HRV biofeedback 15 min daily) were carried out over a period of three months. The third group (control) applied usual care. The primary outcome were between-group differences in mean pain intensity (detected by a Numeric Rating Scale, NRS) during menstruation after three months (post-assessment, t2). Secondary outcomes were the use of analgesics, quality of life (SF-12) and heart rate variability. Results: The study involved 60 women, mean age 29.7 years, SD 8.0 (n = 23 rhythmical massage, n = 20 biofeedback, n = 17 control). For the primary outcome there was a significant difference between the groups after three months (p = .005). Bonferroni adjusted post-hoc tests revealed a significant difference between rhythmical massage and control group (mean difference: -1.61; 95 CI: -2.77/-0.44; p = .004; ES: -0.80). No significant differences were found between rhythmical massage and biofeedback (mean difference: -0.71; 95 CI: -1.82/ 0.40; p = .361; ES: -0.34) and between biofeedback and control group (mean difference: -0.90; 95 CI: -2.10/-0.30; p = .211; ES: -0.51). For the secondary outcomes no significant differences were found between the groups at t2. The drop-out rate was higher in the biofeedback group (n = 6) than in the massage (n = 2) or the control group (n = 4). Conclusion: Preliminary evidence suggests that rhythmical massage might improve pain intensity after 12 weeks compared to usual care.